2015
DOI: 10.1002/mds.26359
|View full text |Cite
|
Sign up to set email alerts
|

GBA Variants are associated with a distinct pattern of cognitive deficits in Parkinson's disease

Abstract: Background Loss-of-function mutations in the GBA gene are associated with more severe cognitive impairment in PD, but the nature of these deficits is not well understood and whether common GBA polymorphisms influence cognitive performance in PD is not yet known. Objectives/Methods We screened the GBA coding region for mutations and the E326K polymorphism in 1,369 PD patients enrolled at 8 sites from the PD Cognitive Genetics Consortium. Participants underwent assessments of learning and memory (Hopkins Verba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
169
6
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(193 citation statements)
references
References 45 publications
14
169
6
4
Order By: Relevance
“…Our findings should be considered in the context of several large-scale studies that describe more rapid cognitive decline in patients with PD who are heterozygotes for mutations in GBA 1 [2931]. This cognitive decline has tentatively been linked to diminished lysosomal acid glucosidase activity, but if this were the causal explanation, then one would expect patients with PD in the context of established GD to show consistent early decline of their cognitive powers.…”
Section: Discussionmentioning
confidence: 62%
“…Our findings should be considered in the context of several large-scale studies that describe more rapid cognitive decline in patients with PD who are heterozygotes for mutations in GBA 1 [2931]. This cognitive decline has tentatively been linked to diminished lysosomal acid glucosidase activity, but if this were the causal explanation, then one would expect patients with PD in the context of established GD to show consistent early decline of their cognitive powers.…”
Section: Discussionmentioning
confidence: 62%
“…GBA -related PD ( GBA -PD) is overall associated with more prominent cognitive decline than idiopathic PD (Alcalay et al, 2012; Brockmann et al, 2011; Saunders-Pullman et al, 2010; Schapira, 2015; Sidransky et al, 2009; Winder-Rhodes et al, 2013), including an increased risk for both mild cognitive impairment (Alcalay et al, 2012) and dementia (Brockmann et al, 2011; Crosiers et al, 2016; Mata et al, 2016; Seto-Salvia et al, 2012). This includes worse performance on broad screening measures of cognitive functioning (e.g., the Montreal Cognitive Assessment; Brockmann et al, 2011), and more specifically, deficits in visual short-term memory (Zokaei et al, 2014), memory and visuospatial functioning (Alcalay et al, 2012; Mata et al, 2016), and executive functioning and working memory (Mata et al, 2016). In addition, GBA -PD is related to neuropsychiatric symptoms such as depression and anxiety (Brockmann et al, 2011; Swan et al, 2016), and those with GBA -PD are more likely to have hallucinations and sustained cholinesterase inhibitor use (Barrett et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that in carriers of "severe" mutations (p.L444P, p.G377S, splicing mutation IVS10+1G>T) the risk of dementia was 5.6 times higher when compared to PD noncarriers, and 2.9 times higher when compared to carriers of "mild" mutations (p.N370S) [63]. There is poor agreement on the role of the GBA polymorphisms E326K on cognition: one study found that both E326K patients and GBA mutation patients have a higher risk of cognitive deterioration [75], another found that the association between GBA and cognitive decline was significant in E326K patients but not in PD patients with GBA mutations [53] and, finally, patients with PD and GBA mutations but not E326K or other polymorphisms progress to dementia more rapidly than non-carriers [52]. Specific cognitive profiles have been associated with GBA mutations in PD patients: one study focused on memory and visuospatial domains [10], while another on abstraction and orientation domains [61].…”
Section: Non Motor Featuresmentioning
confidence: 99%
“…Specific cognitive profiles have been associated with GBA mutations in PD patients: one study focused on memory and visuospatial domains [10], while another on abstraction and orientation domains [61]. Impairment in working memory, executive function and visuospatial abilities seemed to be a characteristic of PD both with GBA mutations and E326K variant [75]. Deficits in visual short-term memory seemed to be present both in GBApositive individuals without PD and GBA-negative patients with PD, but with different characteristics; moreover, GBA-positive individuals who developed PD showed a worse performance overall, leading the authors to hypothesize a "double hit" model [76].…”
Section: Non Motor Featuresmentioning
confidence: 99%